The Effect of Glucose Fluctuation on Apoptosis and Function of INS-1 Pancreatic Beta Cells - Kim, Mi Kyung (Korean Diabetes Association, 2010)
BACKGROUND: Blood glucose level continuously fluctuates within a certain range in the human body. In diabetes patients, the extent of such fluctuation is large, despite the strict control of blood glucose. Blood glucose fluctuation has been shown to mediate more adverse effects on vascular endothelial cells and diabetes complications than chronic hyperglycemia, which has been explained as due to oxidative stress. As few previous studies have reported the effects of chronic and intermittent hyperglycemia on the apoptosis and function of pancreatic beta cells, this study reported herein was performed to investigate such effects on these cells. METHODS: For chronic hyperglycemia, INS-1 cells were cultured for 5 days with changes of RPMI 1640 medium containing 33 mM glucose every 12 hours. For intermittent hyperglycemia, the medium containing 11 mM glucose was exchanged with the medium containing 33 mM glucose every 12 hours. Apoptosis was assessed by TUNEL assay Hoechst staining and cleaved caspase 3. Insulin secretory capacity was assessed, and the expression of Mn-SOD and Bcl-2 was measured by Western blotting. RESULTS: In comparison to the control group, INS-1 cells exposed to chronic hyperglycemia and intermittent hyperglycemia showed an increase in apoptosis. The apoptosis of INS-1 cells exposed to intermittent hyperglycemia increased significantly more than the apoptosis of INS-1 cells exposed to chronic hyperglycemia. In comparison to the control group, the insulin secretory capacity in the two hyperglycemic states was decreased, and more with intermittent hyperglycemia than with chronic hyperglycemia. The expression of Mn-SOD and Bcl-2 increased more with chronic hyperglycemia than with intermittent hyperglycemia. CONCLUSION: Intermittent hyperglycemia induced a higher degree of apoptosis and decreased the insulin secretory capacity more in pancreatic beta cells than chronic hyperglycemia. This activity may be mediated by the anti-oxidative enzyme Mn-SOD and the anti-apoptotic signal Bcl-2.